Mild hyperbaric oxygen enhances recovery of the plantaris muscle atrophy induced by cast immobilization of the hindlimb in male rats - Ai Takemura; Tatsuro Egawa; Ryo Takagi; Ryota Iyama; Zhao Haiyu; Shinichiro Suzuki; Reika Fujino; Takuya Fukunaga; Tatsuya Hayashi; Satoshi Fujita (Physiological Reports)
Abstract Loss of muscle mass is associated with muscle functional decline and mortality. The present study aimed to determine whether exposure to mild hyperbaric oxygen (MHO) during and after casting immobilization reduces muscle atrophy. We distributed eight‐week‐old rats into control (CON), cast immobilization (Cast), and Cast + MHO (1.3 atmosphere absolute with 38% oxygen) groups. Rats were cast for 2 weeks under the normal or MHO condition, followed by a two‐week recovery period under the same condition after cast removal. The plantaris muscle weight (mg/g BW) decreased by approximately 11.5% in the Cast group compared to the CON group (p < 0.01), while there were no differences between the CON and Cast + MHO groups, suggesting that MHO enhanced the recovery of muscle atrophy. However, the soleus muscle weight (mg/g BW) decreased by casting immobilization, regardless of MHO. The enzyme activity by succinate dehydrogenase (SDH) staining in the plantaris muscle was lower in the Cast group than in the CON group (p < 0.01), while there were no differences between the CON and Cast + MHO groups. In summary, MHO enhances the recovery of plantaris muscle atrophy and partially attenuates the decreased SDH activity after cast immobilization of hindlimb in rats.